The Impact of Vitamins E and C Supplementation on Endometrial Thickness in Mice Undergoing High-Intensity Exercise - Gan David; Khemkhaeng; Maria; Santrina Purba (Trigin Institute, 2024)
This study investigates the impact of antioxidant supplementation with vitamins E and C on endometrial thickness in mice subjected to high-intensity exercise. Endometrial health plays a crucial role in reproductive physiology, and exercise-induced alterations in endometrial thickness can have implications for fertility outcomes. A total of X female mice were randomly assigned to experimental groups receiving a combination of vitamins E and C or placebo, while control groups remained sedentary. Endometrial thickness was measured using non-invasive imaging techniques and validated through histological analysis. Statistical analysis revealed significant differences in endometrial thickness between experimental groups, with mice receiving antioxidant supplementation demonstrating an increase in endometrial thickness compared to controls. Furthermore, variations in endometrial thickness were observed among different exercise groups, highlighting the impact of exercise intensity on reproductive physiology. These findings suggest that antioxidant supplementation may mitigate exercise-induced alterations in endometrial thickness, potentially preserving endometrial integrity and enhancing reproductive function. The study underscores the importance of considering exercise intensity and duration in modulating reproductive health and offers translational implications for clinical practice and future research endeavors aimed at optimizing fertility outcomes in physically active individuals.